2020
DOI: 10.1101/2020.08.02.233098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of machine learning and genome-scale metabolic modeling identifies multi-omics biomarkers for radiation resistance

Abstract: Resistance to ionizing radiation, a first-line therapy for many cancers, is a major clinical challenge. Personalized prediction of tumor radiosensitivity is not currently implemented clinically due to insufficient accuracy of existing machine learning classifiers. Despite the acknowledged role of tumor metabolism in radiation response, metabolomics data is rarely collected in large multi-omics initiatives such as The Cancer Genome Atlas (TCGA) and consequently omitted from algorithm development. In this study,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…The metabolome is an excellent integrative system to predict plant environment because it carries imprints of omic inferences and environmental influences (Kosmacz et al ., 2020; Lewis & Kemp, 2021). Ecological metabolomics aims to study the environmental impact on metabolic responses, acclimation and adaptation processes in natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome is an excellent integrative system to predict plant environment because it carries imprints of omic inferences and environmental influences (Kosmacz et al ., 2020; Lewis & Kemp, 2021). Ecological metabolomics aims to study the environmental impact on metabolic responses, acclimation and adaptation processes in natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to postulate that cancers with poor responses to radiotherapy may be more likely to have either strong basal antioxidant defenses or a great deal of metabolic plasticity that facilitates rewiring of metabolic fluxes to generate a powerful antioxidant response after radiation. In agreement with this idea, two recent studies using personalized genome‐scale metabolic flux models identified tumor redox metabolism as a major predictor for radiation sensitivity 106,107 . It appears that tumors with poor radiation response reroute metabolism to boost the levels of reducing factors of the cell, such as NADPH and glutathione, thus enhancing the clearance of ROS 106 .…”
Section: Changes To Major Metabolic Pathways Induced By Ionizing Radiationmentioning
confidence: 82%
“…Therefore, in this study, CBM‐derived fluxomics is used to integrate with multi‐omics datasets in the ML classifier. [ 144 ]…”
Section: Synergisms Of Cbm and MLmentioning
confidence: 99%